RETRACTED: Effect of histone deacetylase inhibitors trichostatin A and valproic acid on hair cell regeneration in zebrafish lateral line neuromasts - He, Yingzi; Cai, Chengfu; Tang, Dongmei; Sun, Shan; Li, Huawei (Frontiers in Cellular Neuroscience, 2014)
In humans, auditory hair cells are not replaced when injured. Thus, cochlear hair cell loss causes progressive and permanent hearing loss. Conversely, nonmammalian vertebrates are capable of regenerating lost sensory hair cells. The zebrafish lateral line has numerous qualities that make it well suited for studying hair cell development and regeneration. Histone deacetylase (HDAC) activity has been shown to have an important role in regenerative processes in vertebrates, but its function in hair cell regeneration in vivo is not fully understood. Here, we have examined the role of HDAC activity in hair cell regeneration in the zebrafish lateral line. We eliminated lateral line hair cells of 5-day post-fertilization larvae using neomycin and then treated the larvae with HDAC inhibitors. To assess hair cell regeneration, we used 5-bromo-2-deoxyuridine (BrdU) incorporation in zebrafish larvae to label mitotic cells after hair cell loss. We found that pharmacological inhibition of HDACs using trichostatin A (TSA) or valproic acid (VPA) increased histone acetylation in the regenerated neuromasts following neomycin-induced damage. We also showed that treatment with TSA or VPA decreased the number of supporting cells and regenerated hair cells in response to hair cell damage. Additionally, BrdU immunostaining and western blot analysis showed that TSA or VPA treatment caused a significant decrease in the percentage of S-phase cells and induced p21Cip1 and p27Kip1 expression, both of which are likely to explain the decrease in the amount of newly regenerated hair cells in treated embryos. Finally, we showed that HDAC inhibitors induced no observable cell death in neuromasts as measured by cleaved caspase-3 immunohistochemistry and western blot analysis. Taken together, our results demonstrate that HDAC activity has an important role in the regeneration of hair cells in the lateral line.